Method for the isolation of highly purified Salmonella flagellins. - Ibrahim, G F (J Clin Microbiol, 1985)
Ten different Salmonella serotypes were grown in a chemically defined medium supplemented with 0.01% yeast extract. After sedimentation of the cells by centrifugation, flagella were detached by exposure to pH 2 for 30 min at room temperature. The flagellaless cells were removed by centrifugation, and the flagellin in the supernatant was further purified by high-speed centrifugation, ammonium sulfate precipitation, and dialysis in 50,000-molecular-weight-cutoff tubing. The 10 flagellin preparations were of a high degree of purity, as demonstrated by electron microscopy, sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and measurement of salmonella H and O agglutination titers of antisera raised in rabbits with the flagellin preparations as immunogens. IMAGES: